2022
DOI: 10.3389/fmars.2022.856483
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Morphological Characteristics on Target Strength of Chub Mackerel (Scomber japonicus) in the Northwest Pacific Ocean

Abstract: Chub mackerel (Scomber japonicus) is an important commercial fish in the Northwest Pacific Ocean. Accurate target strength (TS) underpins acoustic stock assessment but the TS of S. japonicus is still poorly understood. In this study, the Kirchhoff-ray mode (KRM) model was used to estimate the TS of S. japonicus and its relationship with sound wave frequency and fish morphology. The results revealed that TS values varied with pitch angle shifts, with the impact on fish scattering strength being greater at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Reported TS measurements at b 20 using the tethered method included −64.1 dB at 25 kHz and −65.5 dB at 100 kHz for lengths of 23.0–26.8 cm [19] and −67.2 dB, −69.9 dB, −66.9 dB, and −71.1 dB for lengths of 26.2–38.3 cm at 50, 75, 120, and 200 kHz, respectively [20]. A previously reported KRM model used for frequencies of 38, 70, 120, and 200 kHz for S. japonicus TS (FL=15.4–26.2 cm) b 20 yielded −66.02, −66.50, −66.00, and −67.35 dB, within 1 dB of the present study’s results [22], while another study reported values 5–6 dB lower, indicating significant outcome differences based on model parameters [7].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Reported TS measurements at b 20 using the tethered method included −64.1 dB at 25 kHz and −65.5 dB at 100 kHz for lengths of 23.0–26.8 cm [19] and −67.2 dB, −69.9 dB, −66.9 dB, and −71.1 dB for lengths of 26.2–38.3 cm at 50, 75, 120, and 200 kHz, respectively [20]. A previously reported KRM model used for frequencies of 38, 70, 120, and 200 kHz for S. japonicus TS (FL=15.4–26.2 cm) b 20 yielded −66.02, −66.50, −66.00, and −67.35 dB, within 1 dB of the present study’s results [22], while another study reported values 5–6 dB lower, indicating significant outcome differences based on model parameters [7].…”
Section: Discussionsupporting
confidence: 76%
“…Chub mackerel swimbladders were previously reported as showing a long extension, bending below the vertebral column, with a volume-to-body ratio of 3.2%, length ratio of 25%, and posture angle of 11.9° [20]. The reported range of body length of 18 specimens was 12.98∼22.17 cm, with a mean of 16.08 ± 3.15 cm (mean ± SD); the SBL range was 1.45∼6.63 cm, with a mean of 3.64 ± 1.49 cm; and the swimbladder tilt angle was 1.7° to 14.0°, with a mean of 8.26° ± 3.62° [7]. Although both of these studies lack SBH/SBL results, the SBL/SL findings of our study also classify our specimens as having round swimbladders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant factor affecting the TS of T. jarbua is the pitch angle, which is related to the individual size, swimming posture as well as living conditions [39]. In this study, two classic types of pitch angle distributions were adopted to calculate the average TS of T. jarbua [34].…”
Section: Discussionmentioning
confidence: 99%
“…The KRM model was adopted to quantify the TS variation of walleye pollock (Theragra chalcogramma) for elaborating the influence of its ontogeny, physiology, and behavior [38]. In addition, it was also used to evaluate the impacts of morphological characteristics on the TS of chub mackerel (Scomber japonicus) [39].…”
Section: Introductionmentioning
confidence: 99%